Key figure of mobility: the flâneur. (February 2017) - Coates, Jamie
Abstract : The flâneur acts as a key figure for understanding the relationship between the individual, modernity and the city. A reference to dandy young gentlemen, who walked, performed and loitered within the arcades of late 19th‐century Paris, the flâneur has transitioned from a literary and theoretical figure to one used in mobile urban ethnographies. The flâneur, traditionally male, is a figure of pedestrian mobility whose sensorial and mobile engagements with the urban landscape generate distinct forms of creative practice. For this reason, the flâneur has been invoked in relation to the methods and experiences of the ethnographer, who moves and takes note in similar ways. This paper conducts a review of extant literature on the flâneur in ethnographic research, which shows a strong connection between this key figure and its ties to a European tradition dealing with Anglo‐European (post)modernities. It has also inspired a range of methodological innovations in urban ethnography more broadly. Finally, through the case of Tokyo, the paper asks the question of who is drawn to flânerie and who is deterred from it, demonstrating how the transgressive potentialities of flânerie are only desirable for some.